ANALISIS CACAT PENYUSUTAN TERHADAP DESAIN CASING GEARBOX DENGAN SIMULASI METODE DIE CASTING - Bara Muhammad, (2020)
Gearbox casing is one that will accommodate the mechanical components of a transmission. Cases must be made with the best precision to avoid misalignment. In this study, the gearbox casing uses LM24 material by manufacturing using the die casting method. The purpose of this study was to determine the defective results of several casting mold designs to obtain optimal results from the design in casting the gearbox casing. In the initial design with a single channel, the system produces 2.44% shrinkage defects and scattered defects in the workpiece to produce an optimal design by minimizing the shrinkage defects to redesign the design. In design improvement 1 by changing the location of the gating system produces shrinkage defects of 1.84%. Then a second and third repair design was carried out by adding to the pad system 4 and 8 respectively with the result of 1.84% shrinkage and 1.54% addition of the pad system successfully reducing the number of shrinkage defects in the workpiece. Furthermore, to get more optimal results, adding 3 risers with 0.79% shrinkage defect results. Design improvement 4 proved to be quite optimal compared to the initial design which produced more shrinkage defects of 2.44%.